The Application of Vacuum Valve Technology as AFR Settings in 3500 Watt Electric Generator Operated by Methane Gas - Tri Widagdo; Eka Satria Martomi; Ella Sundari; Selastia Yuliati (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
The scarcity of fuel oil, especially the gasoline type, is now a national problem that needs to be solved. This is caused by the rapid growth of industry and transportation. On the other hand, the problem of handling wet garbage has not been maximal, causing pollution that can disrupt health. The impact of this problem is felt also in the use of household-scale generators that operate using gasoline fuel. This study aims to convert gasoline to methane gas in the operation of a 3500 Watt Generator (Electric Generator Set). Methane gas (CH4) is obtained from the gasification process of wet waste. The method used for the AFR (Air-Fuel Ratio) regulator is the use of vacuum valve components. The use of this method cannot be separated from the easy aspects of the maintenance/repair, easy to make and cheap price. The target to be achieved in this research is to get performance data of generators operated with Methane gas fuel. The generator which is used as a research object is a generator household scale with a maximum power of 3500 Watt. Results variables to be observed among other: engine efficiency as well as optimum engine AFR generator. Furthermore, the data is compared with the data generated generator that uses gasoline fuel. This research is an experimental study, starting with the design of the vacuum valve component, followed by the installation of the component on the generator machine and ending with a machine test. The experimental data on the generator with the nominal power of 3500 Watt is: Operated by Gasoline, the optimum power, Popt is 3750 Watt, Max. efficiency, ηmax is 62.2%; AFRopt is 6.7, then operated by methane gas, optimum. power, Popt is 3270 Watt, Max efficiency, ηmax is 66,1%, AFRopt is 7,2. So, gas methane can be used to replace gasoline to operate 3500 Watt generator.